Age-associated pro-inflammatory adaptations of the mouse thoracic aorta - Hemmeryckx, Bianca; Hoylaerts, Marc F.; Deloose, Eveline; Van Hove, Cor E.; Fransen, Paul; Bult, Hidde; Lijnen, H. Roger (Thrombosis and Haemostasis, 2013)
Arterial ageing may be associated with a reduction in vasodilation due to increased reactive oxygen species (ROS) production, whereas endothelial cell activation induces procoagulant changes. However, little is known on the effect of ageing on expression of anticoagulant endothelial markers such as endothelial protein C receptor (EPCR). To study age-associated alterations in smooth muscle cell (SMC) and endothelial cell (EC) structure and function, the aorta was isolated from 10-week-and 12– and 24-month-old C57BL/6J mice and analysed for its expression of genes involved in senescence, oxidative stress production, coagulation and matrix remodelling. In addition, vasorelaxation experiments were performed using 10-week-and 24-month-old thoracic aortic ring segments in organ chamber baths. The media thickness of the thoracic aorta progressively increased with age, associated with hypertrophy of vascular SMCs. Basal nitric oxide production and sensitivity to acetylcholine-mediated vasodilation in thoracic aorta rings was reduced with age, whereas no significant differences in ROS production could be demonstrated. Gene expression of tissue factor, EPCR and von Willebrand factor was not affected by ageing of the aorta, whereas that of thrombomodulin was mildly reduced and that of xanthine dehydrogenase, NADPH oxidase 4, tumour necrosis factor-α and vascular cell adhesion molecule-1 significantly enhanced. In conclusion, a reduction in endothelial cell-mediated vasodilation in aged thoracic aortas of C57BL/6J mice was accompanied by a shift towards a pro-inflammatory state of the endothelium.
Keywords: Vascular ageing; C57BL/6J mice; endothelial dysfunction; EPCR